Valence fluctuations in Sn(Pb)2P2S6 ferroelectrics - Yevych, R.; Haborets, V.; Medulych, M.; Molnar, A.; Kohutych, A.; Dziaugys, A.; Banys, Ju.; Vysochanskii, Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The valence fluctuations which are related to the charge disproportionation of phosphorous ions P4+ + P4+ → P3+ + P+5 are the origin of ferroelectric and quantum paraelectric states in Sn(Pb)2P2S6 semiconductors. They involve recharging of SnPS3 or PbPS3 structural groups which can be represented as half-filled sites in the crystal lattice. Temperature–pressure phase diagram for Sn2P2S6 compound and temperature-composition phase diagram for (PbySn1–y)2P2S6 mixed crystals, which include tricritical points and where a temperature of phase transitions decrease to 0 K, together with the data about some softening of low energy optic phonons and rise of dielectric susceptibility at cooling in quantum paraelectric state of Pb2P2S6 are analyzed by GGA electron and phonon calculations and compared with electronic correlations models. The anharmonic quantum oscillators model is developed for description of phase diagrams and temperature dependence of dielectric susceptibility.